The practice of internal marketing communications in an SME Rural Bank a study of its branch network - Tongco, Luis Cui (2007.)
"This research is an inquiry into the employee centric practice of internal marketing communication (IMC) in the context of a rural bank retail branch network. While majority of the scholarly works in IMC have focused on formal communication campaigns, this study delved into both formal and informal practices which explicitly and implicitly shape internal marketing activity. The three core concepts of IMC emphasized in this study are:communication, motivation, and learning and development as made manifest in the workplace. Furthermore, this study explores the role of leadership characteristics and relationship dynamic in driving the internal marketing communication processes. The researcher gathered and analyzed qualitative feedback from various types of employees in the rural bank representing the top management, middle managers, and frontline staff. Rural banks situated in both urban and rural areas were also examined to further ascertain the role if IMC. The results of the study indicated that informal practice is prevalent in the rural bank setting and is primarily driven by certain leadership characteristics of its top managers. As strategic decision makers, the senior managers create the service goals and establish the service processes necessary to turn these ideals into concrete and workable action steps for their employees.Central to executing IMC are the middle managers who serve as critical communication channels. The managers' interpersonal characteristics and openness to information sharing influence the clarity of understanding, initiative, and workplace learning of employees. Moreover, the effective implementation of IMC requires a human approach to employees and a genuinely caring disposition. Specifically, traits such as considerate leadership, communication openness, and coaching on the job have all contributed to greater employee productivity through increased ownership of job tasks and greater team cohesion among the branch employees. While findings have shown that the informal ractice of IMC is a practical approach to improving service quality and employee performance among small to medium enterprises or SME's, the results also suggest that formal practices may support and strengthen the prevailing informal managerial style. Establishing formal and strandardized processes such as performance management systems and secret shopper programs may complement to the informal management style of the bank's leaders and managers since it serves as a concrete and objective basis for performance. Formal activities do not necessarily water down the personal and relationship driven approach akin to small and medium businesses. This study presents a fresh approach to internal marketing communications by presenting a workable fdefinition of IMC in the informal context and by providing a conceptual model which exploits the synergy between the three related core concepts of IMC. The conceptual model is also extended to include other application of IMC as a human and managerial approach and a personal and relationship-driven process."
Thesis (Ph.D. Communication)--University of the Philippines, Diliman.
Keywords: Communication in marketing; Interpersonal communication; Communication in small business